Peran kualitas pelayanan terhadap kepuasan pelanggan pada usaha warung makan - Hanifah, Nurul (Maliki Interdisciplinary Journal, 2024)
This research discusses the important role of service quality in consumer satisfaction at Warung Bu Nur. As time goes by, competition in the food business is getting tighter so traders must have an advantage so that consumers are interested and satisfied with the quality of service and quality of the products provided